The Role of Afghanistan in Central Asia: Risks and Future Prospects Overview (International relations and international law Journal, 2024)
In the International landscape Afghanistan encompasses a faltering polity with several arguments that support this claim. The state is known as the buffer state and a landlocked country, which is currently under the umbrella of the Taliban regime. The Central Asian Countries are specifically apprehensive and nervous regarding the uncovered system in Afghanistan, notably considering the withdrawal of international powers in 2014 and then in 2021. Central Asia exemplifies an intricate interplay of risks, challenges, and future. Similarly, this research paper highlights the geopolitical landscape of Afghanistan within the context of Central Asia, emphasizing both the current risks and potential opportunities for the region’s prospects. Besides, it also investigates the challenges and critical rebukes of modern international relations in Central Asia, while exploring avenues for the progress of the scenario examined in the proposed study. However, the researcher employed a descriptive method of inquiry, collecting secondary data from meritorious journals. The research study would be wholesome in analyzing alternatives of Afghanistan and Central Asian ties addressing regional challenges for modern international relations. Thus, the researchers would base new avenues for upcoming related domains in scholarly research. In this way, the present study is limited to investigating Afghanistan in central Asia, navigating its influence with the risk and prospects. It plays a key role in underscoring Afghanistan’s new journey with the Taliban, which aims to globalize the world under new leadership.Key words: Afghanistan, Central Asiа, South Asian region, risks, prospects.